2021
DOI: 10.1051/e3sconf/202126402030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Design of Concrete with Hybrid Steel and Basalt Fiber

Abstract: Adding different fiber types may yield improvement of steel fiber reinforced concrete (SFRC) features. Therefore, the investigation of hybrid fiber reinforced concrete (HFRC) mechanical properties is relevant. The effect of adding hybrid steel and basalt fiber on the mechanical properties of fine-grained concrete is studied. It is shown that hybrid fiber reinforcement using optimal steel and basalt fiber ratio allows preventing concrete mixtures' segregation and improving their structure homogeneity. This, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…18, Issue 1, 111-136 [3,4]. The results of the compressive strength at the age of 28 days for mixtures that contain steel fibers showed that the concrete mixture (0 % D.S + 1 % S.F.L) has achieved the highest compressive strength of 74.9 MPa (46.8 % greater than reference specimen), and it also higher than the mixtures (0 % D.S + 1 % S.F.S) and (0 % D.S + 1 % H.S.F) by 13.8 %, 15.4 %, respectively, these results are in agreement with other studies [6,10,11,12].…”
Section: Civil and Environmental Engineeringsupporting
confidence: 92%
“…18, Issue 1, 111-136 [3,4]. The results of the compressive strength at the age of 28 days for mixtures that contain steel fibers showed that the concrete mixture (0 % D.S + 1 % S.F.L) has achieved the highest compressive strength of 74.9 MPa (46.8 % greater than reference specimen), and it also higher than the mixtures (0 % D.S + 1 % S.F.S) and (0 % D.S + 1 % H.S.F) by 13.8 %, 15.4 %, respectively, these results are in agreement with other studies [6,10,11,12].…”
Section: Civil and Environmental Engineeringsupporting
confidence: 92%